New Spectroscopic Insight into the Deactivation of a ZSM‐5 Methanol‐to‐Hydrocarbons Catalyst. Issue 11 (4th May 2021) - Zachariou, Andrea; Hawkins, Alexander P.; Suwardiyanto,; Collier, Paul; Barrow, Nathan; Howe, Russell F.; Parker, Stewart F.; Lennon, David
Abstract: The nature of the hydrocarbon pool at different stages of the methanol‐to‐hydrocarbons reaction over ZSM‐5 is examined. A combination of reaction testing, analytical and spectroscopic techniques is employed to investigate changes in the nature and form of the hydrocarbon pool as a function of reaction conditions and reaction time. It is shown that inelastic neutron scattering spectroscopy (INS) complements other spectroscopic methods for observing molecular components in the hydrocarbon pool of working catalysts. INS is uniquely able to spectroscopically identify the form of coke species present in deactivated catalysts. Abstract : Pool time ! Characterising the hydrocarbon pool of the Methanol‐to‐Hydrocarbons reaction over a ZSM‐5 catalyst. The vibrational fingerprint of the hydrocarbon pool present in the catalyst in steady state conditions as well as the vibrational spectrum of a catalyst well within the deactivation stage is identified and characterized via inelastic neutron scattering spectroscopy.